Application of reverse osmosis in food processing - Ali, Noorhalieza; Hassan, Onn (Faculty of Chemical & Natural Resources Engineering, 1991)
Reverse osmosis is only recently used in the food industry and is gaining interest. This article treats the various effects of the physical properties of food towards the permeation flux of water, the apparatus used together with methods of improving their performance. Lastly, a study of the concentration of whey and milk is included